Memory and the abyss of communication: Philosophers' collective memory, citation and meaning attribution. Issue 2 (8th December 2011) - KYPRIANIDOU, EFI
Are there certain kinds of memory that impose conditions in communicative exchanges? In this article I address this issue having as a reference case the well known debate between J. Derrida and J. R. Searle. Through the pages of the exchange, Searle appeals to what he conceives as social memory of (his) philosophical tradition and to the memory of his teacher J. L. Austin, as his (sole) intellectual legatee and authorized spokesman. On the other hand, Derrida 'stretches' the practice of citation - a procedure normally mentioned as a mnemonic practice. In the exchange, memory is supposed to function as a constraint to the meaning attribution. But can it really play that role? Does any kind of memory constrain the meaning of Searle's (and Derrida's) words? By reading the Searle-Derrida debate as an exemplary case, and focusing on aspects of Derrida's thought, we argue that the idea of an introspective memory given, which because it appears justifies the formulation of memory beliefs, proves to be intrinsically unreliable. Therefore, we argue that the idea that memory beliefs logically constrain the ascription of meaning is undermined.